2019
DOI: 10.1111/srt.12668
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive analysis of skin proteins in healthy Chinese subjects using an Orbitrap Fusion Tribrid mass spectrometer

Abstract: Objective The objective of this study was to perform noninvasive analysis of skin proteins in a healthy Chinese population using label‐free nanoflow liquid chromatography‐mass spectrometry (nLC‐MS). Materials and Methods Five consecutive tape strippings were obtained from the volar forearm skin of healthy Chinese subjects. Proteins were extracted, and trypsin‐digested peptides were analyzed by a nanochromatography instrument coupled to an Orbitrap Fusion Tribrid mass spectrometer. Data‐dependent acquisition al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Digested peptides were fractionated using an Ultimate 3000 system (Thermo Fisher Scientific, Waltham, MA, USA) [57]. Peptide fractions were analysed by online nanospray LC-MS/MS on an Orbitrap Fusion coupled to an EASY-nano-LC system (Thermo Scientific, Waltham, MA, USA) [58]. Proteome Discoverer software 2.0 (Thermo Fisher, Shanghai, China) [59] was used to process the raw MS/MS data obtained.…”
Section: Proteomics Analysismentioning
confidence: 99%
“…Digested peptides were fractionated using an Ultimate 3000 system (Thermo Fisher Scientific, Waltham, MA, USA) [57]. Peptide fractions were analysed by online nanospray LC-MS/MS on an Orbitrap Fusion coupled to an EASY-nano-LC system (Thermo Scientific, Waltham, MA, USA) [58]. Proteome Discoverer software 2.0 (Thermo Fisher, Shanghai, China) [59] was used to process the raw MS/MS data obtained.…”
Section: Proteomics Analysismentioning
confidence: 99%
“…As mentioned, its complexity results in difficulties in separating and homogenizing the tissue for mass spectrometric analyses, and the dominance of structural proteins further complicates the process. Consequently, until recently, prior studies have only identified a relatively small fraction of the expressed skin proteome [21,22,33,[35][36][37][38][39]. For example, Mikesh et al [33] analyzed the composition in three skin layers from two anatomical regions, resulting in characterization of about 200 proteins and providing insight into varying protein composition depending on skin layer and skin region.…”
Section: Proteomic Analysis Of Healthy Human Skinmentioning
confidence: 99%
“…Indeed, AD patients with reduced content of DCD suffer from recurrent Staphylococcus aureus infections [21]. Although proteolytically cleaved forms of DCD have been characterized as major AMPs in sweat [22], the uncleaved form is also reportedly detectable in the upper epidermis of healthy individuals [23]. DCD has specific antimicrobial activity against pathogenic species of Staphylococcus, Escherichia, Pseudomonas, Candida, and Listeria spp.…”
Section: Introductionmentioning
confidence: 99%